Learning by doing: observing an interprofessional process as an interprofessional team. Issue 3 (May 2014) - Brennan, Caitlin W.; Olds, Danielle M.; Dolansky, Mary; Estrada, Carlos A.; Patrician, Patricia A.
Abstract New competencies exist for interprofessional education, which are centered on the goal of improving quality of care and patient safety through improved interprofessional collaboration. Interprofessional education and effective interprofessional collaboration are cornerstones of the Veterans Affairs Quality Scholars fellowship program. The purpose of this project was to evaluate an innovative interprofessional education strategy in which teams of physicians and nurses were "learning by doing" as they observed and analyzed the functioning of an interprofessional process, specifically, inpatient discharge. Fellows completed voluntary, anonymous surveys seeking their perspectives about the project. Fellows' feedback revealed several themes, with both positive and negative characteristics related to team functioning, interprofessional understanding, microsystem knowledge, pooled knowledge and assignment challenges. The strength of this strategy is exemplified by the fact that fellows not only learned from each other's separate professional observations, but also observed the emergence of a shared interprofessional perspective through working together.